The oral Pilipino vocabulary of Hiligaynon speaking grade I entrants of Mambusao West District, Capiz - Navarra, Libertad (Kapunan) 1929- (1974)
In this study, sixty Hiligaynon-speaking Grade I entrants were tested to assess the extent of their oral vocabulary in Pilipino which they may have assimilated as a result of exposure to Pilipino mass media and contact with Tagalog-speaking people. The subjects were asked to give oral answers in Pilipino to picture stimuli and structured questions in Hiligaynon.
Thesis (Master of Arts in Teaching)--University of the Philippines.
Keywords: Pilipino language -- Study and teaching